2009
DOI: 10.1086/594120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced Infection Control at 2 Neonatal Intensive Care Units in The Philippines

Abstract: Background The growing burden of neonatal mortality due to hospital acquired neonatal sepsis in the developing world creates an urgent need for low cost effective infection control measures in low resource settings. Methods Using a pre/post comparison design, we measured how rates of staff hand hygiene compliance, colonization with resistant pathogens (defined as ceftazidime- and/or gentamicin-resistant gram-negative rods (GNRs) and resistant gram-positive cocci), bacteremia, and overall mortality changed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 19 publications
(16 reference statements)
2
55
0
6
Order By: Relevance
“…The rates of sepsis in this study are comparable to those in units in Taiwan that reported rates ranging from 3% to 4% [18,19], but lower compared with data from other countries such as the Philippines, The Netherlands, and Nigeria, where sepsis rates have been reported to range from 15.1% to 19.6% [20][21][22]. Furthermore, at 2.68 cases per 1,000 live births, the rate of sepsis for inborn infants was lower than that reported in other countries including Korea (5.9 cases per 1,000 live births) [23], the USA (6.1 cases per 1,000 live births) [4], and India (14.8 cases per 1,000 live births) [24].…”
Section: Discussionsupporting
confidence: 74%
“…The rates of sepsis in this study are comparable to those in units in Taiwan that reported rates ranging from 3% to 4% [18,19], but lower compared with data from other countries such as the Philippines, The Netherlands, and Nigeria, where sepsis rates have been reported to range from 15.1% to 19.6% [20][21][22]. Furthermore, at 2.68 cases per 1,000 live births, the rate of sepsis for inborn infants was lower than that reported in other countries including Korea (5.9 cases per 1,000 live births) [23], the USA (6.1 cases per 1,000 live births) [4], and India (14.8 cases per 1,000 live births) [24].…”
Section: Discussionsupporting
confidence: 74%
“…However, Picheansathian et al [35] and Gill et al [38] reported no improvement in HCAI, but mortality was reduced in the study by Gill et al [38]. Won et al [36] reported an improvement in the total infection rate (bloodstream, surgical, urinary tract, gastrointestinal tract, skin and respiratory tract) from 15.13±0.98 to 10.69±0.88 (p=0.003).…”
Section: Resultsmentioning
confidence: 96%
“…Nine of the included studies reported on blood culturepositive HCAIs [29,[32][33][34][35][36][37][38] or colonisation by pathogens [34]; seven of these reported a decrease in the incidence of HCAI following implementation of interventions to improve HHC. However, Picheansathian et al [35] and Gill et al [38] reported no improvement in HCAI, but mortality was reduced in the study by Gill et al [38].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies solely measured a change in healthcare professionals' behaviour (Kirkpatrick level 3) as an outcome measure (Muto et al 2000;Huang et al 2002;Sharek et al 2002;Rosenthal et al 2003;Won et al 2004;Danchaivijitr et al 2005 The remainder looked at the broadly defined change in nosocomial infection rates (Helder et al 2010;Zhang et al 2010), risk of death per 1000 ICU admissions (Gill et al 2009), catheter-related blood stream infections (Lobo et al 2005;Bhutta et al 2007;Lobo et al 2010) and changes in rates of MRSA, vancomycin-resistant enterococci (VRE) and Clostridium difficile (Doron et al 2011). …”
Section: Analysis Of Coded Data From Included Studiesmentioning
confidence: 99%
“…Infections can be transmitted from a colonised healthcare professional (a qualified individual who delivers professional health care in a systematic way to any individual in need of healthcare services) to a susceptible patient as a result of direct physical contact, such as when bathing or caring for a patient (direct-contact transmission) or transmitted from a colonised object to a susceptible patient, such as needles or gloves (indirect-contact transmission). The most common organisms transmitted via direct-contact transmission are Clostridium difficile (Whitaker et al 2007) and methicillin-resistant Staphylococcus aureus (MRSA; Larson et al 2000;Gill et al 2009). The most commonly acquired HCAI are urinary tract infections, surgical site infections (including MRSA) and pneumonias (including ventilator-associated pneumonia; Reilly et al 2007).…”
Section: Introductionmentioning
confidence: 99%